Media Weblog sebagai Sumber Belajar Bahasa Inggris pada Matakuliah Perhotelan Di Prodi Pendidikan Bahasa Inggris IKIP Budi Utomo Malang - Tities Hijratur Rahmah; Ike Dian Puspita Sari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2019)
Mastering English actively will make us easy in a business and communicate with people from any country, and able to master all the knowledge we absorb like by socializing with anyone and wherever we are. And one of the most profound fields of English skills is English for hospitality known as the English for hotels. It is very clear why hospitality is so related to English. In modern era, the use of technology can be used for the learning process. Such a phenomenon leads students to be able to learn English wherever and whenever they want to have a discussion or read to get the information they want. This study contains the development of Hospitality material in the form of a weblog for students of English Language Education, IKIP Budi Utomo Malang. The researcher developed material based on a development model developed by Borg and Gall (1983). Borg and Gall (1983). Data from this study will be analyzed qualitatively. In each unit there are sub-sub topics or sub-units with reading skills, writing, listening and speaking. There are also some exercises to practice speaking in the form of dialogue and answering questions based on descriptions that can develop student’s vocabulary for speaking English. The final product is designed as attractive as possible by presenting images and colors that can make students interested. The results of interviews from students are that they like the hospitality class and they can learn wherever and whenever they want to read, because they can easily access material through cell phones. Students are very enthusiastic about learning English for hotels because at the moment the hospitality business is very rapidly developing